The necrotic gene in Drosophila corresponds to one of a cluster of three serpin transcripts mapping at 43A1.2. - Green, C.; Levashina, E.; McKimmie, C.; Dafforn, T.; Reichhart, J.M.; Gubb, D. (Genetics, 2000)
Mutants of the necrotic (nec) gene in Drosophila melanogaster die in the late pupal stage as pharate adults, or hatch as weak, but relatively normal-looking, flies. Adults develop black melanized spots on the body and leg joints, the abdomen swells with hemolymph, and flies die within 3 or 4 days of eclosion. The TOLL-mediated immune response to fungal infections is constitutively activated in nec mutants and pleiotropic phenotypes include melanization and cellular necrosis. These changes are consistent with activation of one or more proteolytic cascades. The nec gene corresponds to Spn43Ac, one of a cluster of three putative serine proteinase inhibitors at 43A1.2, on the right arm of chromosome 2. Although serpins have been implicated in the activation of many diverse pathways, lack of an individual serpin rarely causes a detectable phenotype. Absence of Spn43Ac, however, gives a clear phenotype, which will allow a mutational analysis of critical features of the molecular structure of serpins.